The Bony Density of the Pedicle Plays a More Significant Role in the Screw Anchorage Ability Than Other Regions of the Screw Trajectory - Zan Chen; Yue Chen; Jiajun Zhou; Yanwei He; Jingchi Li (Orthopaedic Surgery)
ABSTRACT Objective Osteoporosis is a crucial risk factor for screw loosening. Our studies indicate that the bone mineral density (BMD) in the screw trajectory is a better predictor of screw loosening than the BMD of the lumbar spine or the screw insertion position. Research has shown that anchorage on the screw tip is the most significant factor for screw anchorage ability, while others argue that decreased bony quality in the pedicle poses a significant risk for screw loosening. This study aimed to determine whether the bony quality of the screw tip, pedicle, or screw‐anchored vertebral body plays the most significant role in screw anchorage ability. Methods A total of 73 patients who underwent single–segment bilateral pedicle screw fixation, along with posterior and transforaminal lumbar interbody fusion (PLIF and TLIF), from March 2019 to September 2020 were included in this retrospective study. The Hounsfield unit (HU) value of the fixed vertebral bodies, the entire screw trajectory, screw tip, screw–anchoraged vertebral body, and pedicles were measured separately. Data from patients with and without screw loosening were compared, and regression analyses were conducted to identify independent risk factors. Additionally, the area under the curve (AUC) values were computed to assess the predictive performance of different parameters. Furthermore, fixation strength was calculated in numerical models with varying bony densities in different regions. Results HU values were found to be significantly lower in the loosening group across most measuring methods (HU values in the pedicle, 148.79 ± 97.04, 33.06 ± 34.82, p < 0.001). Specifically, the AUC of screw loosening prediction was notably higher when using HU values of the pedicle compared to other methods (AUC in the pedicle > 0.9 and in the screw insertion position > 0.7). Additionally, computational results for fixation strength revealed a clear decline in screw anchorage ability in models with poor BMD in the pedicle region. Conclusions Pedicle bone quality plays a more significant role in screw anchorage ability than that in other regions. The innovation of bony augmentation strategies should pay more attention to this region to optimize the screw anchorage ability effectively.